(untitled) (Conferencea, 2023)
This article is focused on the analysis of the problems and their observations in the teaching of computer science and information technologies during the teaching process. It is hoped that this analysis will serve as a guide for authors, teachers, consultants and other interested persons. In the article, common problems in the teaching of Informatics and Information Technology in secondary schools, such as: Provision of teaching materials: With the rapid development of Informatics and Information Technologies, the compilation of current and latest news into teaching materials and access to them is important. This article highlights the challenges of updating, developing, and making these materials accessible to institutions.